1987
DOI: 10.1002/em.2860090311
|View full text |Cite
|
Sign up to set email alerts
|

Factors that affect the frequency of thioguanine‐resistant lymphocytes in mice following exposure to ethylnitrosourea

Abstract: The frequency of thioguanine(TG)-resistant lymphocytes in mice treated with ethylnitrosourea (ENU) was followed for a period of 51 wk using our clonogenic assay [Jones et al, 1985a,b]. The effects of dose (0-58 mg/kg), time since treatment (2-51 wk), dose rate (5 weekly X 11.7 mg/kg versus 1 X 58 mg/kg), and age at time of treatment (3 vs 15 mo) on the frequency of TG-resistant, concanavalin A-responsive spleen cells were evaluated. The frequencies of TG-resistant spleen cells were generally dose responsive fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
35
1

Year Published

1990
1990
1998
1998

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 28 publications
8
35
1
Order By: Relevance
“…The Hprt-mutant fraction in control animals was =2 x 10-6; this is similar to the values reported previously for the BALB/c (1) and C57BL/6 (2, 3) mouse strains. Mutant frequency in treated animals was =35-fold higher (7.3 x 10-5), similar to previously reported values obtained with ENU (2). Reconstruction experiments showed that the PE of mutants on plates containing 6TG was indistinguishable from the PE on the PE plates (data not shown), thus demonstrating that the observed mutation frequencies measured in our experiments are good approximations of true mutation frequency existing in the T-cell populations.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…The Hprt-mutant fraction in control animals was =2 x 10-6; this is similar to the values reported previously for the BALB/c (1) and C57BL/6 (2, 3) mouse strains. Mutant frequency in treated animals was =35-fold higher (7.3 x 10-5), similar to previously reported values obtained with ENU (2). Reconstruction experiments showed that the PE of mutants on plates containing 6TG was indistinguishable from the PE on the PE plates (data not shown), thus demonstrating that the observed mutation frequencies measured in our experiments are good approximations of true mutation frequency existing in the T-cell populations.…”
Section: Resultssupporting
confidence: 77%
“…Nevertheless, at the present time we cannot exclude the possibility that some of the mutations observed could have resulted from in vitro replication of DNA containing extremely persistent DNA adducts. However, this seems unlikely given the stable mutation frequency observed in mice up to a year after ENU exposure (2). If replication of promutagenic lesions in vitro were contributing a substantial fraction to the total number of observed mutations, then one would anticipate that the mutation frequency would decrease with time as adducts were slowly repaired.…”
Section: Mutationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, there is trafficking of cells between different lymphoid tissues, uneven expansion and turnover of individual lymphocyte clones, and a moderate selection pressure against the mutant phenotype [Freitas and Rocha, 1993;Deubel et al, 19961. In rodents, it is also unclear in which organs and tissues lymphocyte mutations are induced [Jones et al, 1987;Aidoo et al, 1991, 19931. The types of mutations produced in rodent lymphocytes by simple alkylating agents appear to reflect the damage produced by these compounds Mittelstaedt and Heflich, 1994;Mittelstaedt et al, 1995;Jansen et al, 19951.…”
Section: Introductionmentioning
confidence: 98%
“…Jones and co-workers (1)(2)(3) have demonstrated that cloning mouse lymphocytes permits analysis of mutations in the hprt gene that have occurred in vivo in T-cell progenitors. Possibilities and limitations of this method were investigated, and preliminary results on the mutant frequency in gammairradiated animals will be given.…”
Section: Introductionmentioning
confidence: 99%